أثر القيادة الاستراتيجية على تحسين جودة الخدمة (دراسة ميدانية في وزارة الأوقاف والشؤون الدينية بسلطنة عُمان): THE IMPACT OF STRATEGIC LEADERSHIP ON IMPROVING SERVICE QUALITY (A CASE STUDY IN THE MINISTRY OF WAQIF AND RELIGIOUS AFFAIRS IN THE SULTANATE OF OMAN) - Muhammad Al Mashikhi, , Faisal Said; Kamri, Nor'Azzah; Lubis, Asmuliadi (Online Journal of Islamic Management and Finance (OJIMF), 2024)
This study aimed to identify the impact of strategic leadership in improving and developing the quality of service in the Ministry of Waqif and Religious Affairs in the Sultanate of Oman from the point of view of the ministry's employees. A sample of 249 employees in the Ministry of Waqif and Religious Affairs was randomly selected to answer questionnaire which is consisting of 57 items as a tool for data collection. Descriptive analytical approach and regression were used for entering, processing and analysing data. Results illustrated a good level of strategic leadership and quality of service in the Ministry of Waqif and Religious Affairs. The study also demonstrated the existence of a positive relationship between the five dimensions of strategic leadership and the quality of service provided in the ministry, ranging between medium and weak. Finally, results revealed that there was a significant effect of determining the strategic direction, supporting organizational culture and promoting ethical practices as dimensions of strategic leadership in the quality of service provided by the ministry, while the effect of the other two dimensions of strategic leadership (development of human capital and investment of strategic resources and capabilities) was weak and ineffective on Quality of service. The study presented many recommendations, including the need for all employees to participate in drawing up strategic policies and paying attention to attracting competencies and developing local capabilities working in the ministry and adopting strategic policies based on the latest electronic means and social media to reach the beneficiaries of the ministry's services in a more effective manner in implementation and achievement of Oman 2040 vision.